RELEGIOUS MODERATION IN THE IMPLEMENTATION OF ISLAMIC RELIGIOUS EDUCATION AND MORAL EDUCATION AT THE SENIOR HIGH SCHOOL/VOCATIONAL SCHOOL LEVEL - Armedi, Rama; Kawakip, Ahmad Nurul; Asrori, Mohammad (UIN ANTASARI BANJARMASIN, 2025)
Islamic Religious Education is a strategic medium for introducing and teaching the values ​​of religious moderation to students. The values ​​of religious moderation must be manifested in Islamic Religious Education textbooks. The values ​​contained in the Islamic Religious Education and CharacterBuilding textbook for Senior High School/Vocational High School Grade X are Tawasuth (moderation), i'tidal (justice), tasamuh (tolerance), and tawazun (balance). Meanwhile, moderate values ​​that can be integrated into learning include Tolerance-Based, Business Ethics, Persistence and Simplicity, and Reflection and Discussion Activities. These values ​​are certainly very relevant and need to be integrated into every textbook, not only limited to the textbooks analyzed in this study. Theoretically, this research provides a practical contribution in formulating policies for the preparation of more inclusive and moderate Islamic Religious Education teaching materials. As recommendations for further research, it can examine textbook revisions, teacher training, and further research using fieldwork.